2019
DOI: 10.1002/jcla.23077
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and virulence factors of methicillin‐resistant Staphylococcus aureus isolated from patients with bacteremia

Abstract: Background The various virulence factors of methicillin‐resistant Staphylococcus aureus bacteremia (MRSAB) are associated with a high mortality rate worldwide. Further studies are warranted to confirm the significant relationship between the strains and virulence genes. Here, we prospectively investigated the molecular characteristics underlying the genotypes and virulence factors of MRSA isolated from patients with bacteremia. Methods We collected 59 MRSA isolates from adult patients with bacteremia. Antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…It has been reported that MRSA strains differed in their carriage of enterotoxin and leucotoxin encoding genes. Consistent with previous reports (Song et al, 2016;Kim et al, 2020), the majority (92.9%) of ST72 MRSA strains carried identical staphylococcal enterotoxin and leukotoxin encoding genes: seg, sei, sem, sen, seo, and LukED; only LukED was predominant in the ST188 MRSA strains. We also found that the majority of ST30-IV MRSA isolates carried sei (100%) and LukED (87.5%) genes.…”
supporting
confidence: 90%
“…It has been reported that MRSA strains differed in their carriage of enterotoxin and leucotoxin encoding genes. Consistent with previous reports (Song et al, 2016;Kim et al, 2020), the majority (92.9%) of ST72 MRSA strains carried identical staphylococcal enterotoxin and leukotoxin encoding genes: seg, sei, sem, sen, seo, and LukED; only LukED was predominant in the ST188 MRSA strains. We also found that the majority of ST30-IV MRSA isolates carried sei (100%) and LukED (87.5%) genes.…”
supporting
confidence: 90%
“…However, all strains of ST72 showed susceptibility to tetracycline. Several studies ( Kim et al, 2020 ; Lim et al, 2012 ; Park et al, 2007 ) also reported that the ST72 type isolates were susceptible to tetracycline. ST72 is the most reported type in Korea, and is widely prevalent in clinical environment, livestock products, and soil ( Ko et al, 2011 ; Lim et al, 2010 ).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, in recent years, the existence or absence of the lukF-PV gene has made no difference in virulence; thus, we suggest that there are pathogenic factors other than the lukF-PV gene [52]. High drug resistance was strongly associated with the virulence factors of S. aureus [53]. The POT index -106-137-80 was the most frequently isolated and is the most frequently isolated and commonly reported in hospitals in Japan [54,55].…”
Section: Plos Onementioning
confidence: 67%